ANALISIS YURIDIS TENTANG PERETASAN DATA PRIBADI PENUMPANG LION AIR - Michael Leunard; Sari Mandiana; Jusup Jacobus Setyabudhi (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
In the era of information explosion through information technology and communication by means of the internet, information and self-identity is very easy, it can be obtained both for the benefit of the owner of personal data and business interests. One of the cases is the case of the personal data of a Lion Air passenger that has been hacked. The personal data of Lion Group's passengers, namely Marindo Air, Lion Air, Thai Air which covers 7.8 million personal data of passengers from countries including Indonesia, have been hacked by groups of irresponsible people. Legal consequences for victims of Lion Group passengers by hacking of personal data written in Article 26 of the ITE Law which regulates the protection of personal data, but in Article 26 of the Law ITE does not contain a criminal threat that can be imposed on someone when using other people's personal data information without the relevant consent. The personal data protection bill The personal data protection bill is very much needed, that is special protection, because personal data is part of the human rights issue in consideration of the personal data protection draft law .Keywords: Due to the law; Personal Data Hacking; Lion Air Passenger..